Sistem Pendidikan Agama Islam di Dunia Barat: Sebuah Tinjauan Kualitatif - Azhar, Dzul; Bahij, Muhammad Alfan; Hasan, Ismail; Hanani, Hanif (Lembaga Yasin AlSys, 2024)
Today, in western society, religion is more prominent in an individual sense. The purpose of this paper is to provide insight into how religious education can be implemented in Islamic communities by looking at events occurring in the western world today. Even though capitalism and secularism continue to try to expand their influence throughout the world, humans still try to maintain the religious feeling that has been there since birth. Even in an individual context, religious attitudes and behavior begin to take on new meaning. Of course, the state of society and the serious problems facing humanity play an important role in this. Because religion has always been on of the strongest sources of motivation for individuals an society, and will continue to be so. In addition, the increasing diversity in western society and the development of democratic rights and freedoms throughout the world are also factors that positively influence the development of religion.